Lattice-gas Monte Carlo study of adsorption in pores - Trasca, Raluca A. (2004)
A lattice-gas model of adsorption inside cylindrical pores is evaluated with Monte Carlo simulations. The model incorporates two kinds of sites: (a line of) “axial” sites and surrounding “cylindrical shell” sites, in the ratio 1:7. The adsorption isotherms are calculated in either the grand canonical or canonical ensembles. At low temperature, there occur quasitransitions that would be genuine thermodynamic transitions in mean-field theory. Comparisons between the Monte Carlo and mean-field theory results for the heat capacity and adsorption isotherms are provided.